Thermal analysis and phase formation of eco-friendly cold-bonded high-calcium fly ash–calcium hydroxide lightweight aggregate at various curing time - Chalermphan Narattha (2020)
© 2019, Akadémiai Kiadó, Budapest, Hungary. The research on fly ash lightweight aggregate has been of great interest recently due to its potential for use as a substitute for natural aggregate in concrete mixes. In this work, thermogravimetric analysis of cold-bonded high-calcium fly ash lightweight aggregate with and without minor use of calcium hydroxide was investigated. Calcium hydroxide was used at 5 and 10% to replace part of fly ash. Thermogravimetric analysis measurements were carried out on samples at 0, 3 and 28 days. The results showed that calcium silicate hydrate phase in fly ash–calcium hydroxide mix is higher than reference fly ash mix. This is due to the reaction of calcium hydroxide which helps accelerate the pozzolanic reaction of fly ash. Calcium silicate hydrate was also shown to increase with curing time. Moreover, calcium hydroxide and minor calcium carbonate peaks can also be seen in all mixes while the highest amount of calcium hydroxide was found in the 90FA10CH mix.